2017
DOI: 10.1016/j.fct.2017.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium inhibits placental trophoblast cell migration via miRNA regulation of the transforming growth factor beta (TGF-β) pathway

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…19 In addition, JEG3 cells have been a key model for understanding how environmental toxicants, such as inorganic arsenic, PFAS, and cadmium, impact placental function. 18,[20][21][22] Of importance, a large effort is currently underway by the U.S. Environmental Protection Agency (EPA) to reduce, refine, and replace animal testing for chemical safety research with in vitro assays. A key step towards this goal is understanding how in vitro conditions impact internal accumulation of toxic substances such as PFAS and, ultimately, affect the translational capacity of in vitro toxicological assessments.…”
mentioning
confidence: 99%
“…19 In addition, JEG3 cells have been a key model for understanding how environmental toxicants, such as inorganic arsenic, PFAS, and cadmium, impact placental function. 18,[20][21][22] Of importance, a large effort is currently underway by the U.S. Environmental Protection Agency (EPA) to reduce, refine, and replace animal testing for chemical safety research with in vitro assays. A key step towards this goal is understanding how in vitro conditions impact internal accumulation of toxic substances such as PFAS and, ultimately, affect the translational capacity of in vitro toxicological assessments.…”
mentioning
confidence: 99%
“…Consequently, miRNAs have been proposed as biomarkers of Cd induced kidney injury (Fay et al, 2018). Furthermore, Cd exposure altered the expression of several miRNAs in human placenta and placental trophoblasts (Brooks et al, 2016;Brooks and Fry, 2017). This suggests that deregulation of miRNA-based mechanisms could be important in Cd pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…2A). Earlier studies have identified transcriptional alterations of miRNAs due to Cd exposure (Brooks et al, 2016;Brooks and Fry, 2017;Fay et al, 2018). However, systematic analyses of the differentially expressed miRNAs and their target genes have not been carried out thus far.…”
Section: Exposure Downregulates Mir-30 Family Mirnasmentioning
confidence: 99%
“…Until now, most studies focused on chemical exposures including cadmium [57], phthalates [58], arsenic [59], and endocrine disrupting chemicals [60] in association with placental miRNAs. Moreover, multiple studies confirm a role for miRNAs in the response to air pollution exposure in adults [6163].…”
Section: Air Pollution-induced Placental Epigenetic Alterationsmentioning
confidence: 99%